Performance and Feeding Cost Analyses of Starter Broiler Chicks Fed Diets Containing Graded Levels of Raw Sandbox Seeds (Hura crepitans) As a Source of Methionine - Jimoh, A.; Okwupa, I.T.`; Angevbee, E.I.; Bumkeng, E.I.; Gbakaan, E.N. (Nigerian Journal of Animal Science, 2023)
A study was conducted to assess the performance and feeding cost analyses of starter broiler chickens fed diets containing graded levels of sandbox seed (SBS) as a source of methionine. Four dietary treatments labelled T1, T2, T3 and T4 were prepared such that SBS was included at 0%, 0.1%, 0.2% and 0.3% respectively. One hundred and twenty unsexed day-old Ross 308 broiler chicks were randomly distributed to the four dietary treatments in a completely randomized design. Proximate analysis and amino acid profile of the sandbox seeds were determined. Initial body weight, feed intake, weight gain and Feed Conversion ratio (FCR) were also determined. Data were also collected on feed cost, feed cost per bird and feed cost per weight gain. All data collected were subjected to one way ANOVA suitable for a completely randomized design using the Statistical Package for Social Sciences. Proximate analysis shows that the seed has 24.63% crude protein, 10.39% crude fiber, 26.38% Nitrogen-free extract, 27.81% ether extract and 4.79% total ash. The SBS has all the essential amino acids. There were no significant differences (p>0.05) among the treatments in their effects on total feed intake (940.00g-1048.89g), final weight (440.00g-485.19g), weight gain (403.30-447.92g) and FCR (2.20-2.50). Although there was marginal decrease in the cost of feed per kilogram as the inclusion level of SBS increases (₦372.60, ₦370.70, ₦368.80 and ₦368.54 respectively), the feed cost per bird (₦363.77-₦386.56) and feed cost per kilogram weight gain (₦819.26-₦920.69) were not significantly different (p>0.05) among the treatments. It was concluded that SBS has good nutritional potential and could serve as a source of methionine in poultry feeding.